PEMAHAMAN SOSIOPRAGMATIK TERHADAP PENGGUNAAN BAHASA DALAM MEDIA SOSIAL INSTAGRAM DI KALANGAN GENERASI Z - Damayanti, Fina; Saleh, Muhammad (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to: (1) Describe the language usage patterns of Gen Z on Instagram, (2) Analyse the sociopragmatic aspects that emerge through this language, (3) Identify the social and cultural impacts of the language created by Gen Z on Instagram. The approach used is a qualitative method with case study techniques, in-depth interviews in Achjar et al. (2023), and social media content observation. The results show that the language used by Gen Z on Instagram is not only a means of communication but also a means of expressing social identity, norms, and group attitudes. In the research by Apyunita & Asdah (2025), innovative digital language, such as slang, abbreviations, mixed codes, and emoticons, marks a sociopragmatic dynamic that is rich in social meaning. This research provides an important understanding of language interaction and social context in modern digital communication.